Prevalence of social media addiction and its related factors among students of nursing and midwifery in Iranian context: A cross-sectional study - Reza Toumari; Farhad Ramezani-Badr; Giampiera Bulfone; Kourosh Amini (Shahrekord University of Medical Sciences, 2023)
Background and aims: This study aimed to identify the status of social media addiction (SMA) and some related factors in nursing and midwifery students in Iran. Methods: In this cross-sectional study, 284 Nursing and Midwifery students participated. The study was conducted from October 4, 2021 to February 16, 2022. Sampling was done by simple random method. The data collection tool was Bergen's Social Media Addiction Scale (BSMAS). Data analysis was performed using SPSS version 22. Pearson correlation and multivariate linear regression tests were used to analyze the data. Results: 234 (82.39%) of the students had some level of social media addiction. There was a statistically significant relationship between the hours of using social media during the day and the duration of using these media with addiction (β=0.537, P<0.001). There was a significant relationship between SMA and living single and independently (β=0.58, P=0.032). SMA had no significant relationship with other demographic characteristics of students (P>0.05). A statistically significant relationship was also between SMA and students' academic performance (β=-0.412, P<0.001). Conclusion: The prevalence of SMA in the study population was alarmingly high. This emerging social problem should be considered in the community of nursing and midwifery students. Because this type of addiction can affect the quality and quantity of nursing care, with the development of attractive social networks dedicated to education and learning, these networks should be directed toward useful student goals.